Cationic Antimicrobial Peptides of Respiratory Tract Nonspecific Defense System: Defensins and Cathelicidins. Defensins - Molecules Undergoing a Renaissance (Part 5) - A.Ye. Abaturov (Zaslavsky O.Yu., 2012)
This review presents the contemporary data characterizing pathogenetic value and sanogenetic contribution of defensins' participation in development of respiratory tract diseases.